2022
DOI: 10.1136/archdischild-2021-323493
|View full text |Cite
|
Sign up to set email alerts
|

Trends in weight loss attempts among children in England

Abstract: ObjectivesTo describe trends in reported weight loss attempts among school-aged children and to investigate its sociodemographic determinants.DesignWe analysed data of children who participated in the Health Survey for England from 1997 to 2016 (n=34 235). This repeated cross-sectional survey reported weight loss attempts and sociodemographic characteristics. Body weight and height were measured by trained interviewers, and body mass index for age z-score was calculated. Multivariable logistic regression was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…They found that girls were more likely to engage in weight-loss behavior in 2001/2002, but that this gender difference reduced over time, with more boys attempting to lose weight during 2017/2018 [30]. In contrast, a UK-based study that compared weight-loss attempts between two periods (1997/1998 and 2015/2016) indicated that the number of these attempts increased over time and were more common among girls [31].…”
Section: Discussionmentioning
confidence: 99%
“…They found that girls were more likely to engage in weight-loss behavior in 2001/2002, but that this gender difference reduced over time, with more boys attempting to lose weight during 2017/2018 [30]. In contrast, a UK-based study that compared weight-loss attempts between two periods (1997/1998 and 2015/2016) indicated that the number of these attempts increased over time and were more common among girls [31].…”
Section: Discussionmentioning
confidence: 99%
“…It is intended that parents will feel more con dent in how to handle such conversations and, as a result, less anxious of the impact on their child's wellbeing of other steps they may take to improve children's health (e.g., when making changes to the family's diet or physical activity that may happen without the need to discuss weight). Importantly, it is intended that children will have more positive and supportive experiences in talking about their own weight with their parents or carers which may be an important part of reducing the increases in children's weight dissatisfaction (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…However, the case for providing the guidance for parents that we have reported here is relevant and important whether or not such systems exist; HCPs report the need for guidance for parents based on their one-to-one practice experience (49), and many parents who do perceive their child to be overweight have not learned this through national programmes. Further, as rates of children's weight concern and weight loss attempts increase (17), parents of children of all weights may wish to seek advice on how to help their children to develop more positive self-perceptions and behaviours in relation to their body size and weight. Other work with children and young people, for example through work conducted with 630 young people by the Royal College of Pediatrics and Child Health (RCPCH) State of Child Health (Healthy Weight), corroborates the nding that when they are consulted, many children are interested in the opportunity to check whether or not their weight is healthy through routine checks (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, providing this feedback and raising parental awareness about a child’s weight can lead to angry and upset responses from some parents [ 11 13 ], and has been criticised due to the association between parents’ and children’s perceptions of being overweight, and poorer mental health outcomes in children [ 14 , 15 ]. While no specific association between such measurement programmes and the development of children’s weight dissatisfaction has been identified, weight control behaviours among children and adolescents have increased over recent years [ 16 , 17 ]. Parents report fears that the measurement and feedback process may trigger unplanned conversations with their child about weight that would not otherwise have happened, which may be sufficient to start a sequence of events that negatively impact their child’s wellbeing [ 11 ].…”
Section: Introductionmentioning
confidence: 99%